2014
DOI: 10.2139/ssrn.2443280
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Policy and Export Performance in Efficiency-Driven Economies

Abstract: Increased globalisation of trade has led a growing number of firms to search beyond their traditional domestic markets. As a result, export-led growth has gained focus, particularly amongst industrialising nations, or so-called efficiencydriven economies, in search of economic growth. Policy prescriptions have generally proposed a weakening of the exchange rate as a means to stimulate exports; whilst an exchange rate appreciation would be detrimental to exports and encourage imports. Past research on this topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Although a number of studies (e.g., Genc and Artar, 2014;Bahmani-Oskooee and Ardalani, 2006) have endorsed a favorable relationship between exchange rate devaluations and export performance, other studies have pointed to the limited changes in export performance following exchange rate movements in some economies. Rowbotham et al (2014) examined this relationship for a sample of nine efficiency-driven economies, all of which had floating exchange rate regimes, for the period 1990-2009. Using panel data models and fixed effects, their results showed that a weaker exchange rate does not necessarily improve export performance.…”
Section: Macroeconomic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of studies (e.g., Genc and Artar, 2014;Bahmani-Oskooee and Ardalani, 2006) have endorsed a favorable relationship between exchange rate devaluations and export performance, other studies have pointed to the limited changes in export performance following exchange rate movements in some economies. Rowbotham et al (2014) examined this relationship for a sample of nine efficiency-driven economies, all of which had floating exchange rate regimes, for the period 1990-2009. Using panel data models and fixed effects, their results showed that a weaker exchange rate does not necessarily improve export performance.…”
Section: Macroeconomic Studiesmentioning
confidence: 99%
“…The literature on exchange rate and exports is abundant and inconclusive. At the macroeconomic level, while several studies have endorsed a favorable relationship between exchange rate devaluations and export performance (Genc and Artar, 2014;Bahmani-Oskooee and Ardalani, 2006), others have pointed to the limited changes in export performance following exchange rate movements in some economies (Rowbotham et al, 2014;Loto, 2011). Across Middle East and North African (MENA) countries, studies tend to rely mainly on aggregate data rather than firm-level data (El-Ramly, 2008;Bahmani-Oskooe and Kandil, 2009;Nouira et al, 2011;Bahmani-Oskooee et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Schaling [23] argues that South Africa's monetary authorities should be interested in targeting competitiveness via the RER which is also correct technique to narrow the present inflation targeting band. Raddats, Schaling & Kabundi, Matlasedi, Ilorah, & Zhanje, and Rowbothan, Saville, & Mbululu [24][25][26], confirmed that exchange rate has a positive effect on South African exports. While, Sekantsi [27], Muzenda, Chamunorw & Choga, Chiloane, and Khosa confirmed a negative effect.…”
Section: Relevant Empirical Literaturementioning
confidence: 91%
“…Ref. [11] assessed exchange rate policy and export performance in efficiency driven economy uses fixed effects method and panel data model concluded that a weakening of the exchange rate does not necessarily improve export performance. Also export growth seems to be associated with stronger exchange rates.…”
Section: Literature Reviewmentioning
confidence: 99%